Surgical site infection in vascular surgery : an exploration of risk factors and nursing interventions - Dobbin-Williams, Karen, 1969- (2009)
Thesis (M.N.)--Memorial University of Newfoundland, 2009. Nursing Includes bibliographical references (leaves 193-209) Background/Objectives: Surgical site infection (SSI) is the third most common type of healthcare-associated infection accounting for approximately 38% of all infections in the surgical patient population. In 2005, the Canadian "Safer Healthcare Now" campaign identified 4 strategies to reduce SSI risk based on available evidence: 1) antibiotic prophylaxis, 2) maintenance of glycemic control in the coronary artery bypass graft surgery population. 3) maintenance of intraoperative normothermia in the colorectal surgery patient population, and 4) appropriate preoperative hair removal. Published research is limited on the use of these four strategies in the prevention of SSIs in vascular surgery patients. The purpose of this study was to determine risk factors for SSI in vascular surgery and to identify nursing interventions to decrease this risk. A secondary purpose was to determine the SSI rate for vascular surgery patients. -- Methods: A sample of 116 was drawn from all vascular surgery patients who underwent Class 1 (clean) vascular surgeries of interest (bypass and abdominal aortic aneurysm [AAA] repair) during 2005. Every second patient from a list with one of these surgeries formed the sample. Paper and electronic charts were retrospectively reviewed, including post discharge records from outpatients clinics, ER, and the Vascular Laboratory. Information on risk factors for SSI, practices related to the management of risk factors, and incidence of SSI was gathered. Standard CDC definitions were used. An attending physician saw 95.7% of patients within 6 weeks of their surgery. -- Results: The SSI rate was 17.2%. Significant SSI risk factors were incorrect timing of antibiotic prophylaxis (p = 0.0068), increased glucose or HbA1c level perioperatively in non-diabetic patients (p = 0.0468), and abrasion in the incisional area preoperatively with no antibiotic prophylaxis (p = 0.0047). Risk factors with a trend but not significant were: not receiving antibiotic prophylaxis with no artificial graft inserted, elevated HbA1c level, hypothermia despite receiving a warming intervention in the post-anaesthesia recovery room (PARR), hypothermia on transfer between units, abrasion in the incisional area preoperatively, emergency procedure, renal/liver disease, increased number of cigarettes smoked, blood loss of 1200-4499 mL, and anemia with blood loss 300-1199 mL. Practice findings included antibiotic prophylaxis was not given to all patients at the correct time or at all, the frequency of glucose and temperature assessments was inconsistent, interventions for hyperglycemia and hypothermia were inconsistently provided and evaluated for effectiveness, aspects of assessment and care were not documented, and policy and protocols for temperature assessment were inconsistently followed. -- Implications: The findings highlight elements of care which might reduce SSI in vascular surgery patients. Improvements are needed in glucose and temperature assessment and control, and antibiotic prophylaxis. Additional research is required with a larger sample size, and on strategies to improve adherence to protocols and policies in existence.